(untitled) (International Journal of Engineering and Computer Science, 2016)
The content based image retrieval (CBIR) is one of the most important research areas of the digital image processing. The content based image retrieval is becoming a new and fast method of information retrieval. The development of the social networking mediums, so many digital images are transitioned and uploaded every day. In order to access the large collection of database, all the oldest searching methods like Google, Bingo, Yahoo are based on the on textual annotation of images. In these tools, all the images are manually annotated with keywords and then retrieved using text-based search methods. Therefore performances of these systems are not satisfactory. So, we need new techniques. These techniques will easy to handle the data and can easily access the data. The CBIR is a technique for retrieving images on the basis of automatically-derived features such as color, texture and shape. It uses digital processing and analysis to automatically generate descriptions directly from the media data. In this paper, we survey some of the technical aspects of content based image retrieval techniques. And also we will discuss the advantages and disadvantages of CBIR methodology.